Presence of the invasive whitefly Aleurocanthus spiniferus (Hemiptera: Aleyrodidae) in Greece. (18th April 2019) - Kapantaidaki, D. E.; Antonatos, S.; Kontodimas, D.; Milonas, P.; Papachristos, D. P.
Abstract : Aleurocanthus spiniferus (Quaintance) (Hemiptera: Aleyrodidae), commonly known as the citrus (or orange) spiny whitefly, is an important pest of various economic crops such as citrus and tea and causes severe economic losses. It is reported for the first time in Greece, in the island of Corfu (North‐West Greece) on sweet orange trees ( Citrus sinensis ). Morphological and molecular data has been used for species identification. Sequences of the mitochondrial cytochrome oxidase I ( COI ) gene from Greek populations have been compared with sequences of the species from Italy and Montenegro, as well as with COI sequences retrieved from GenBank, to examine the genetic diversity of the species. Based on the preliminary results, it appears that the population from Corfu probably arose through several independent introductions. Présence de l'aleurode envahissant Aleurocanthus spiniferus (Hemiptera : Aleyrodidae) en Grèce: Aleurocanthus spiniferus (Quaintance) (Hemiptera : Aleyrodidae), communément appelé aleurode épineux du citronnier, est un organisme nuisible de diverses cultures d'intérêt économique telles que les agrumes et le thé, et causant d'importantes pertes économiques. Il est signalé pour la première fois en Grèce, sur l'île de Corfou (Nord‐Ouest de la Grèce) sur des orangers doux ( Citrus sinensis ). Des données morphologiques et moléculaires ont été utilisées pour l'identification de l'espèce. Les séquences du gène mitochondrial de la cytochrome oxydase de type I provenant des populations grecques ont été comparées à aux séquences de populations de l'espèce provenant d'Italie et du Monténégro, ainsi qu'à des séquences de COI extraites de Genbank, pour examiner la diversité génétique de l'espèce. Sur la base de résultats préliminaires, il est probable que plusieurs introductions indépendantes soient à l'origine de la population de Corfou. Присутствие инвазивной белокрылки Aleurocanthus spiniferus (Hemiptera: Aleyrodidae) в Греции: Aleurocanthus spiniferus (Quaintance) (Hemiptera: Aleyrodidae), обычно известная как цитрусовая (или апельсиновая) колючая белокрылка, является серьезным вредным организмом для различных экономических культур, таких как цитрусовые и чай, и вызывает серьёзные экономические потери. Впервые сообщается о её присутствии в Греции, на острове Корфу (северо‐западная Греция) на деревьях сладкого апельсина ( Citrus sinensis ). Для идентификации вида использовались морфологические и молекулярные данные. Для изучения генетического разнообразия вида митохондриальная цитохромоксидаза гена I греческих популяций сравнивались с последовательностями вида из Италии и Черногории, а также с последовательностями COI, полученными из Genbank. Исходя из наших предварительных результатов, похоже, что популяции Корфу возникли путём нескольких независимых интродукций.